Zabojcze sekrety - Collins, Jackie; Zebrowski, Jerzy (Warszawa : Wydawn. A.A. Kurylowicz ; Katowice : Wydawn. Sonia Draga, 2004)
Polish translation of "Deadly Embrace". A dual prequel-sequel to Lethal Seduction finds celebrity magazine writer Madison investigating her mob hit-man father's past in an attempt to solve the mystery surrounding her mother's death, but encountering a web of greed and deception that soon has her racing for her life.
Translation of: Deadly embrace.
Keywords: Castelli, Madison (Fictitious character) -- Fiction; Women journalists -- Fiction; Mafia -- Fiction; Los Angeles (Calif.) -- Fiction